(untitled) (Biological Sciences - PJSIR, 2001)
A method for the determination of thethickness of gold layerontop of silversubstrate hasbeen developed. Various samples having silver asthe substrate were coated with gold for different time durations by ion sputtering. The gold to silver X-ray counts ratios were determined using an energy dispersive spectrometer equipped to the scanning electronmicroscope. Agraphplotted betweenthegoldto silverX-raycountsratiosandthethickness ofthe gold layers enables to determine the gold layer thickness of anunknown sample by merely measuring its gold to silver X-ray counts ratio and then extrapolating this ratio to itscorresponding thickness.